Medieval English theatre. - Twycross, Meg; Twycross, Meg; Carpenter, Sarah; Carpenter, Sarah; Dutton, Elisabeth M.; Dutton, Elisabeth M.; Kipling, Gordon; Pearce, Michael (Michael Webb); Forse, James H.; Butterworth, Philip (D.S. Brewer, an imprint of Boydell & Brewer Ltd, 2022)
The ludic element of drama in the Middle Ages - or drama with early subject matter - is here to the fore.